AntiBiotic De-escalation in critical care: Effect on outcome, morbidity and mortality of critically ill patients (ABCD Study) / Esther Lim Hui Cheng - Esther Lim , Hui Cheng (2018)
Background: Expanding antimicrobial resistance patterns in the face of stagnant growth in novel antibiotic production underscores the importance of antibiotic stewardship, in which de-escalation remains an integral component. Audit of deescalation therapy in Malaysia is lacking and few centres have an established antimicrobial stewardship program. The frequency of antibiotic de-escalation in the ICU setting of University Malaya Medical Centre (UMMC), a 1643-bedded, tertiary university hospital, was explored. Through this study, a plausible benchmark for deescalation therapy in the local ICU setting can hopefully be established, to provide the basis for future audits and research on the subject. Methods: A prospective, observational study was performed by review of all patients who were admitted to the ICU of UMMC, for clinical or suspected sepsis, between April 2018 and October 2018, by the sole lead investigator. Antibiotic deescalation was defined as the use of narrower spectrum antibiotics, reducing the number of antibiotics, reducing the number of days or the discontinuation of antibiotics after initiation of empirical broad spectrum antibiotics, or a combination of one or more of the above. Subjects dying within 72 hours of antibiotic initiation were considered not de-escalated for subsequent analysis and were subtracted from the study population in determining a modified mortality rate. An electronic collection reporting form (e-CRF) was created using REDcap to key in relevant clinical data. The data was then translated to SPSS for further analysis. Results: A total of 57 subjects were included in this study. iv Primary Outcome: Of the 57 patients studied, 12(21.0%) had their antibiotic regimens de-escalated during their duration of ICU stay, with negative culture being the most likely reason for antibiotic de-escalation (7 of the 12 de-escalated cases). Deescalation was not adversely associated with any of the forms of composite patient outcomes studied - length of ICU and hospital stay, duration on mechanical ventilation, duration on vasoactive drugs and renal replacement therapy, emergence of multi-drug resistant (MDR) micro-organisms, re-infection rates, as well as, mortality. Secondary Outcome: The most commonly suspected source of infection at admission to ICU was Respiratory Tract Infections (52.5%), followed by Gastrointestinal Tract Infections (21.3%). The most commonly prescribed initial empirical antibiotic therapy was penicillin with beta-lactamase inhibitor (31.6%). De-escalation did not significantly affect the total duration of antibiotic therapy. Conclusions: De-escalation of antibiotic therapy was not adversely associated with composite patient outcome measures. It appears safe and prudent for antibiotic deescalation to be carried out in patients with severe sepsis. However, more local studies, including larger sample sizes are required, before reliable benchmarks and conclusions can be drawn regarding antibiotic de-escalation in critical care patients and associated patient outcome in our Malaysian setting. Keywords: Antibiotic de-escalation, Antibiotic stewardship, Benchmark, Prospective observational study, Audit